2021
DOI: 10.1136/bmjopen-2020-046647
|View full text |Cite
|
Sign up to set email alerts
|

Design features that reduce the use of seclusion and restraint in mental health facilities: a rapid systematic review

Abstract: Increasing efforts are being made to prevent and/or eliminate the use of seclusion and restraint in mental health facilities. Recent literature recognises the importance of the physical environment in supporting better outcomes in mental health services. This rapid review scoped the existing literature studying what physical design features of mental health facilities can reduce the use of seclusion and physical restraint.DesignA rapid review of peer-reviewed literature.MethodsPeer-reviewed literature was sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Personalization and freedom of choice, the third parameter, refers to the degree of freedom the client can achieve in a facility ( 37 ). A recent rapid review by Oostermeijer et al ( 38 ) found preliminary evidence that the use of good design and architecture principles can help to prevent measures of seclusion and restraint in psychiatric facilities. The importance of the physical environment in psychiatric settings has also been considered in a safety model of psychiatric care, e.g., the Safewards model ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Personalization and freedom of choice, the third parameter, refers to the degree of freedom the client can achieve in a facility ( 37 ). A recent rapid review by Oostermeijer et al ( 38 ) found preliminary evidence that the use of good design and architecture principles can help to prevent measures of seclusion and restraint in psychiatric facilities. The importance of the physical environment in psychiatric settings has also been considered in a safety model of psychiatric care, e.g., the Safewards model ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the mental health care sector, certain aspects of facility design have been associated with aggressive behaviours, stress levels, use of restraint and seclusion, length of stay, mental health outcomes and resident and staff wellbeing (Connellan et al., 2013; Oostermeijer et al., 2021; Ulrich et al., 2018). The notion of therapeutic design refers to design that is conducive to the mental health, wellbeing and rehabilitation of its residents.…”
Section: Youth Justice Facility Designmentioning
confidence: 99%
“…Described as “spaces of transition,” the psychiatric environment provides stability, space for social interaction, and skill development for patients to successfully transition back to the community ( Chrysikou, 2019 ; Wood et al, 2013 ). The design of psychiatric environments is transforming from a stale institutional environment to healing into therapeutic environments, focusing on design features that result in less aggression and a reduction of the use of coercion (e.g., seclusion or restraint) on the wards ( Oostermeijer et al, 2021 ; Papoulias et al, 2014 ; Seppänen et al, 2018 ; Shepley & Pasha, 2017 ; Shepley et al, 2016 ; Ulrich et al, 2018 ). Based on Ulrich’s work, there has been a recent movement to design psychiatric environments based on healing architecture ( Lundin, 2021 ).…”
Section: Introductionmentioning
confidence: 99%